Socio-demographic Predictors of Health literacy among the Elderly: A Correlational Study - Fatemeh Sharifnia; Mohtasham Ghaffari; Ali Ramezankhani; Sakineh Rakhshanderou (Shahid Beheshti University of Medical Sciences, 2020)
Background and Objective: The elderly people, as one of the most groups at high risk for diseases, need to have a high level of health literacy to having an improved level of health. The aim of this study was to investigate the predictors of health literacy among elderly at health centers affiliated to Shahid Beheshti University of Medical Sciences. Materials and Methods: In this descriptive-analytic study, 270 elderly people were selected via cluster random sampling from health centers affiliated to Shahid Beheshti University of Medical Sciences in Tehran. To collect data, a short form of the S-TOHFLA standard questionnaire was used to measure health literacy. Data were analyzed by SPSS software version 16 via independent t-test, ANOVA, Kendall correlation and multiple regressions. Results: The mean (SD) age of participants was 67 (5/6). The health literacy of the elderly with university education with a mean (SD) 28.2 (7) and the age group of 60-65 years with a mean (SD) 32.6 (4.9), was significantly higher than the other groups (P<0.001). The strongest predictor of health literacy was education, as with an increase in the level of education, the individual's health literacy increased by 0.4 units. In addition, variables such as education, age, economic status and occupation in the regression model were able to predict 45% of health literacy. Conclusion: The study showed that the health literacy score positively correlated with age, female gender, education, education of spouse, employment status, and economic status. The level of education was the strongest predictor of health literacy. DOI: http://doi.org/10.22037/ch.v7i2.22204